Effects of heat-treated β-lactoglobulin and its aggregates on foaming properties - Moro, Andrea (2011)
The effects on foaming properties of the aggregates formed by heating concentrate beta-lactoglobulin solutions (55 mg mL-1, pH 6.8) at 85 °C from 1 to 15 min were investigated. Structural characteristics (size and molecular conformation), hydrophobicity and protein aggregates proportion were also studied. All tested methods pointed at 3 min of heating as a critical time, in terms of conformational changes and aggregation processes. At this time, the most significant conformational changes took place: non-native monomers were present and the greatest amount of dimers and trimers was produced, which was proved with the results of gel densitometry of SDS-PAGE, fluorescence quenching and circular dichroism tests. Foamability and foam stability were both improved by pre-heating the protein. A constant proportion among beta-lactoglobulin species (monomer 51%, dimer 33% and trimer 16%), regardless the protein concentration, led to the same results on foaming properties, confirming the link with structural changes. Aggregates formed by heating beta-lactoglobulin up to 10 min produced more stabilized foams, slowing down disproportionation, because of the formation of stiffer films. The increase in surface hydrophobicity was considered a decisive factor in the improved foamability and hydrophobic interactions improved the foam stability trough the rapid formation of a viscoelastic film. © 2010 Elsevier Ltd.